(untitled) (Revista Iberoamericana de Bioética, 2022)
Palliative sedation is a widely assumed and applied clinical practice in situations that anticipate the end of life. However, despite its benefits when refractory symptoms have no other alternative, on some occasions, sedation give rise to numerous bioethical dilemmas related to the double effect principle that is one of the basic tools, in the field of Bioethics, on which the legality of sedation at the end of life can be based.